National and regional incidence patterns of venous thromboembolism in Finland during 1998–2021 with corresponding mortality trends in 1998–2019 - Lasse Myllylahti; Jari Haukka; Eero Hirvensalo; Riitta Lassila (Thrombosis Update, 2025)
Objectives: Previous research suggest that venous thromboembolism (VTE) -related mortality have been declining over the recent decades, despite the increasing trend of pulmonary embolism (PE) incidence. There is evidence of some regional differences in VTE incidence. We wanted to evaluate the national and regional 21st century VTE incidence in Finland, as well as respective national VTE mortality trends. Patients and methods: In this nationwide registry study, anonymous participants were patients with VTE diagnoses (I26 or I80) during hospital visits or VTE-related documentation of primary cause of death. To assess incidence, we recorded VTE-related hospital visits from the HILMO registry of the Finnish Institute for Health and Welfare. To assess mortality, we recorded deaths with a VTE diagnosis as a primary cause of death from the registries of Statistics Finland. Additionally, we acquired the data about pulmonary CT angiographies from STUK, which is the radiation and nuclear safety authority in Finland. Results: At the national level, the PE incidence doubled during the study period, while the incidence rates of deep vein thrombosis remained stable. Some regional variances in VTE incidence were encountered. The usage of radiological examinations to diagnose PE have become more frequent during the study period. The mortality for VTE peaked in 2004, following the clear declining trend during the follow-up period. Conclusion: Despite the remarkable increase in PE incidence, the mortality rates have been constantly declining from 2004. These results are valuable for the future epidemiological research of VTE.